KONTRIBUSI DANA BANTUAN KEUANGAN TERHADAP PENDAPATAN BUMDes : STUDI KASUS DI KECAMATAN BANTAN: CONTRIBUTION OF RIAU PROVINCE FINANCIAL ASSISTANCE FUNDS ON VILLAGE-OWNED ENTERPRISES' INCOME: CASE STUDY IN BANTAN DISTRICT - Suhadi, Jhon; Ria Nelly Sari; Vince Ratnawati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
Financial assistance from the Riau Provincial Government is allocated according to priorities to provide benefits to villages in the form of accelerating village economic development. Economic development in villages is expected to be able to increase village original income and create community welfare through decent employment opportunities. This study aims to analyze the contribution of financial assistance funds from the Riau Provincial Government and the efforts made by village governments and managers in maximizing these funds to create village original income through Village-Owned Enterprises (BUM Desa). This study uses a qualitative method with a case study approach, data collection through interview techniques, documentation, and audio visuals. Data were analyzed with the help of NVivo 12 software. The results of the study indicate that the objectives of the program and the sustainability of Riau Province's financial assistance funds have contributed, although not optimally. Efforts made by village governments and BUMDes managers include budget planning and utilization, supervision and accountability, transparency, monitoring and evaluation, and community participation. The results of this study are expected to contribute to the Riau Provincial Government in evaluating financial assistance programs in order to improve the management of funds that have been distributed.